2022
DOI: 10.1039/d2gc01345b
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical synthesis of (4S)-N-alkyl-4,5-bis-sulfooxypentanamideviaa one-pot sequential aminolysis-sulfation reaction of (S)-γ-hydroxymethyl-γ-butyrolactone (2H-HBO)

Abstract: The bio-based platform (S)-γ-hydroxymethyl-γ-butyrolactone, whose sustainable kiloscale-synthesis from cellulose-derived levoglucosenone has been validated, is valorized into new potential bio-based surfactants mechano-synthesized in solventless conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In 2022, Wadouachi et al reported the one-pot/two-step mechanochemical synthesis of four potential surfactants (4 S )- N -alkyl-4,5-bis-sulfooxypentanamides 29 from bio-based ( S )-γ-hydroxymethyl-γ-butyrolactone 27 (2H-HBO) in a one-pot two-step process (Scheme 7). 86 This short sequence consisted of an aminolysis of 2H-HBO 27 followed by a disulfation reaction using a PBM. The optimized conditions consisted of grinding 2H-HBO (1 equiv.)…”
Section: Green Metrics Used In Mechanochemical Reactionsmentioning
confidence: 99%
“…In 2022, Wadouachi et al reported the one-pot/two-step mechanochemical synthesis of four potential surfactants (4 S )- N -alkyl-4,5-bis-sulfooxypentanamides 29 from bio-based ( S )-γ-hydroxymethyl-γ-butyrolactone 27 (2H-HBO) in a one-pot two-step process (Scheme 7). 86 This short sequence consisted of an aminolysis of 2H-HBO 27 followed by a disulfation reaction using a PBM. The optimized conditions consisted of grinding 2H-HBO (1 equiv.)…”
Section: Green Metrics Used In Mechanochemical Reactionsmentioning
confidence: 99%
“…In 2022, Wadouachi et al reported the one-pot/two-step mechanochemical synthesis of four potential surfactants (4S)-N-alkyl-4,5-bis-sulfooxypentanamides 29 from bio-based (S)-γhydroxymethyl-γ-butyrolactone 27 (2H-HBO) in a one-pot twostep process (Scheme 7). 58 This short sequence consisted in of an aminolysis of 2H-HBO 27 followed by a disulfation reaction using a PBM. The optimized conditions consisted on grinding 2H-HBO (1 equiv.)…”
Section: Scheme 5: Amidification Synthesis With CDI In Mechanochemistrymentioning
confidence: 99%
“…13 Furthermore, the development of a one-pot two-step strategy for the mechanosynthesis of anionic surfactants was also effective with LGOderived (S)-γ-hydroxymethyl-γ-butyrolactone (2H-HBO (1), Scheme 1) in a planetary ball mill. 14 Indeed, leveraging our expertise in LGO chemistry, we capitalized on biobased lactone 1, which can be easily derived from LGO. 15 Through a mechanochemical transformation, lactone 1 was converted into various diols via an aminolysis reaction with different primary amines.…”
Section: Introductionmentioning
confidence: 99%
“…13 Furthermore, the development of a one-pot two-step strategy for the mechanosynthesis of anionic surfactants was also effective with LGO-derived ( S )-γ-hydroxymethyl-γ-butyrolactone (2H-HBO ( 1 ), Scheme 1) in a planetary ball mill. 14…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation